Identifikasi Faktor Penentu Tingkat Pengangguran Terbuka Di Provinsi DIY Ditinjau Dari Sektor Pariwisata - Syaqfa Afira; Fitri Juniwati Ayuningtyas (FEB Universitas Sultan Ageng Tirtayasa, 2023)
This study aims to analyze the influence of the tourism sector, namely the number of hotels, tourists, travel agents, and tourist objects, on the open unemployment rate in the Province of DIY. The research objects include the Regencies of Sleman, Bantul, Kulon Progo, Gunung Kidul, and the Municipality of Yogyakarta for the 2014-2020 period. The analytical method used is panel data regression. Based on model testing, the results show that the common effect model is the most appropriate to analyze the level of open unemployment in the Province of DIY. The regression results show that the number of hotels and travel agencies has a significant positive effect. In contrast, the number of tourists has a negative effect on the open unemployment rate in the Province of DIY. However, the tourist object variable has no significant effect on the open unemployment rate in the DIY Province.